The Printing Industry / An Introduction to its Many Branches, Processes and Products - Printing Industries Of America; Strauss Victor (1967)
Foreword, Preface, Printing Processes and Methods, Composition for Printing, The Theory and Practice of Full-Color Printing, Graphic Arts Photography, Printing-Image Carriers, Printing Presses, Presswork, Paper and Other Printing Stocks, Printing Inks, Binding and Finishing, Art-and-Copy Preparation, References, Bibliography, Acknowledgements, Index.
Foreword, Preface, Printing Processes and Methods, Composition for Printing, The Theory and Practice of Full-Color Printing, Graphic Arts Photography, Printing-Image Carriers, Printing Presses, Presswork, Paper and Other Printing Stocks, Printing Inks, Binding and Finishing, Art-and-Copy Preparation, References, Bibliography, Acknowledgements, Index.